(untitled) (Journal of Informatics Education and Research, 2025)
Consumption of luxury goods has moved outside the conventional elite group into the aspirational middle class. Emphasizing psychological, social, and cultural elements, this study critically investigates the elements driving luxury consumption. Examining the change in consumer tastes from materialistic possession to experiential luxury, it looks at how prestige, exclusivity, and symbolic value affect buying behavior. It also assesses how consumer perceptions of luxury goods are shaped by marketing techniques, quality impression, and branding. The results give businesses aiming at the shifting luxury market ideas and insights on the dynamics of premium consumption.